Vititecture; re imagining a Swedish dairy farm to a vineyard - Garme-Syri, Shayan; Nordling, Viktor (My University, 2024)
The Swedish countryside has encountered several challenges over the past century. Rural depopulation, caused by people migrating to urban areas in search of better opportunities, has led to shrinking communities and a weakened social fabric. Economic shifts towards industrial farming practices have reduced the number of active farms but increased their size, leaving a considerable number of unused farm buildings scattered throughout the landscape. However, recent years have witnessed a shift towards more sustainable rural development, characterised by the emergence of a new rurality. This modern reinterpretation challenges outdated perceptions and is driven by societal, economic, and technological changes. Rural and agricultural businesses are adapting to these shifts by reinventing themselves to provide not only for nutritional needs but also to offer leisure opportunities, promote environmental sustainability, create post-industrial employment, counteract rural depopulation, and contribute to a sense of history and tradition in regions and nations. Furthermore, a new agricultural program, the Swedish vineyard, has been gaining prominence during the same time period. This development has been facilitated, in part, by climate changes that allow new crops to thrive in the Swedish climate, as well as more permissive policy changes concerning gatesales of alcohol. Given that the typology of the Swedish vineyard is in its early stages, there is a notable scarcity of architectural knowledge specific to this context. This thesis directly engages with the challenges faced by the countryside by working with the building stock of unused farms and implementing the new program of the vineyard. It investigates the current preconditions for establishing vineyards in Sweden, demonstrating its findings through the transformation of a farm in Grimeton, Halland. The farm converts from an inactive dairy farm into a vineyard and winery with associated tasting and commercial businesses. The transformation is executed with a holistic and mindful approach, considering the traditional architecture and craftsmanship of existing farm buildings, ensuring that changes and extensions harmonise with the historical past of the farmyard.